Low‐temperature thermochronology as a control on vertical movements for semi‐quantitative source‐to‐sink analysis: A case study for the Permian to Neogene of Morocco and surroundings. (27th October 2020) - Charton, Rémi; Bertotti, Giovanni; Duval Arnould, Aude; Storms, Joep E. A.; Redfern, Jonathan
Abstract: Continental passive margins and their hinterlands in the Atlantic realm have been the locus of many Low Temperature Thermochronology (LTT) and time‐Temperature (t‐T) modelling studies that evidence pre‐, syn‐ and post‐rift episodic km‐scale exhumation and burial episodes. In this study, we integrate data from over 30 published LTT and t‐T modelling studies from Morocco and its surroundings using a three‐step workflow to obtain: (a) exhumation/burial rates, (b) erosion rates and (c) palaeoreconstructions of source‐to‐sink domains, between the Permian and the Present. Our synthesis of available t‐T modelling results predicts high exhumation rates in the Anti‐Atlas (0.1 km/Myr) during the Early to Middle Jurassic, and in the High Atlas (0.1 km/Myr) and Rif (up to 0.5 km/Myr) during the Neogene. These rates are comparable to values typical of rift flank, domal or structural uplifts settings. During the other investigated periods, exhumation rates in the Meseta, High‐Atlas, Anti‐Atlas and Reguibat shield are around 0.04 ± 0.02 km/Myr. Interpolation of the exhumation rates at the regional scale allow calculation of the volume of rocks eroded. Estimates of erosion rates are between 0.2 x 10 3 and 7.5 x 10 3 km 3 (in the Meseta and the Reguibat Shield respectively). Ten erosional (quantitative, from interpolation results) and depositional (qualitative, from data synthesis) "source‐and‐sink" maps have been constructed, with emphasis on the Jurassic and Cretaceous periods. The maps integrate the extent of exhumed domains, using information from geological maps, lithofacies and biostratigraphic data from new geological fieldwork and well data from onshore and offshore basins. The results illustrate changes in the source‐to‐sink systems and allow for a better understanding of the Central Atlantic margin hinterlands evolution. Abstract : In this study we integrate data from over thirty published LTT and t‐T modelling studies from Morocco and its surroundings using a 3‐step workflow to obtain 1) exhumation/burial rates, 2) erosion rates, and 3) paleoreconstructions of source‐to‐sink domains (Source‐and‐Sink maps), between the Permian and the Present.